The Nexus between union membership and workplace climate. (3rd April 2017) - McMurray, Adela; Scott, Don
ABSTRACT: This paper summarises findings from a study of the relationship between union membership and workplace climate. A survey of 1380 workers in three different Australian manufacturing firms found union membership to be negatively associated with workplace climate in one company, positively associated with workplace climate in another and to have no significant relationship to workplace climate in the third. These results, when linked to the findings from observational research and focus group discussions, indicated that when a business was only partially unionised, internal harmony and good workplace conditions were reasons for the existence of a positive relationship between workplace climate and union membership. However, when union-management relationships were fractious, the workplace climate was driven by that relationship with deleterious results for workplace harmony. The findings highlight the pivotal requirement for management to provide positive work environments and, when unions are involved, to work with them to achieve this outcome.